“Efectos de diferentes dosis de abonos orgánicos en los indicadores morfológicos y productivos de plantas de pimiento (Capsicum annuum l.) cultivadas en macetas.” - Cedeño Tomala, Mariuxi Eloisa (2022)
Urban and peri-urban food production in potted crops have been satisfying the demand for foods such as peppers. According to this, this project proposed the evaluation of different doses of edaphic organic fertilizers like bocashi and worm humus in morpho-productive indicators of pepper plants which are grown in pots. For this, a Completely Randomized Block Design (DBCA) was applied, consisting of seven treatments (T0: Without fertilization, T1: 160 g/Bocashi plant, T2: 320 g/Bocashi plant, T3: 160 g/worm humus plant, T4: 320 g/worm humus plant, T5: 80 g/Bocashi plant + 80 g/worm humus plant and, T6: 160 g/Bocashi plant + 160 g/worm humus plant) and three repetitions with nine experimental units (plants) for each one. An analysis of variance (ANOVA) was carried out, and for the comparison of average between treatments, the Tukey test was applied (P≤ 0.05). The variables evaluated were: plant height (cm), stem diameter (cm), number of fruits, weight of fruits (g), yield (kg/ha), and economic analysis. Regarding the achieved results, it was found that: in plant height, stem diameter, days to flowering, fruit length, fruit diameter, fruit weight, and yield; there were not statistically significant differences, while in the variable number of fruits, T6 managed to surpass statistically the rest of the treatments and even tripled the records of the control (T0). However, in terms of profits, the treatment that presented the highest profitability in the economic analysis was T3. Finally, it is concluded that the dose with the greatest benefits over the rest was presented by 160 g/plant of Bocashi + 160 g/plant worm humus.